Flavonoid, pterocarpans and steroid from Erythrina fusca Lour. growing in Bangladesh: isolation, and antimicrobial and free-radical scavenging activity - A Anjum; M. Z. Sultan; S Ferdosh; M Kaisarul Islam; M. A. Rashid; L Nahar; S. D. Sarker (Institue of Medicinal Plants, ACECR, 2021)
Background: Erythrina fusca Lour. (fam. Fabaceae) is a flowering tree, found extensively in tropical and subtropical Asian countries, and is known for its use in traditional medicine for the treatment of various human ailments, for example, fever, liver complications, infections, and headaches. Objective: To carry out phytochemical study, and antimicrobial and free-radical scavenging activity evaluation of E. fusca. Methods: Ground stem bark of this plant was extracted by maceration with methanol, partitioned with various organic solvents, and compounds were isolated by chromatographic means. Structures of isolated compounds were confirmed by spectroscopic analyses. The antibacterial activity was assessed by the disc diffusion method, and the free-radical scavenging activity was determined by DPPH assay. Results: The carbon tetrachloride soluble fraction of the methanol extract of E. fusca afforded shinpterocarpin (1), lupinifolin (2), 3,9-dihydroxy-4-(3,3-dimethylallyl) [6aR,11aR]-pterocarpan (3) and β-sitosterol (4). Compounds 1-3 showed considerable antimicrobial activity against five Gram-positive and eight Gram-negative bacterial and three fungal strains tested in this study. Compound 1 exhibited the highest zone of inhibition of 19.4 mm against Bacillus subtilis. Additionally, compounds showed free-radical scavenging effects in DPPH assay with the IC50 values of 8.8, 7.7 and 7.9 µg/mL for compound 1, 2 and 3, respectively. However, they displayed some general toxicity in BSL assay. Conclusion: The isolation of bioactive compounds 1-3 supports some traditional medicinal uses of this plant. However, general toxicities found in the BSL assay might raise concerns regarding its safety, while offering a new avenue of future investigation on cytotoxicity of these compounds against human cancer cell lines.